Perceptions and Expectations of International and Ethnically Diverse Students in the Context of Diversity Management Policy Document in a Turkish Foundation University - Bataklar, Sinan; DEVECİYAN, MERİ TAKSİ (Türk Kooperatifçilik Kurumu, 2023)
The aim of this study is to analyse the effects of having policy documents regarding diversity management on students’ perceptions in higher education context. The study was carried out with 25 international students and students with different ethnic backgrounds who have been studying in various undergraduate and associate degree programs of a Turkish foundation university. The data were gathered via open-ended questions and phenomenology method. The data were applied using the qualitative content analysis approach. Based on the analysis of the data, noticeable themes have been reached regarding the students’ perceptions of the university’s diversity management policies and the academic satisfaction they get in the provided learning atmosphere during their time on and off campus. The themes and their sub-themes are as follows: The theme “the presence of the university to provide an inclusive educational atmosphere in the availability of students from different countries and ethnic backgrounds” include the significance of policy documents of the higher education institution, the necessity of an international campus and awareness raising and networking events, the theme “expectations to increase satisfaction about academic processes” includes the sub-themes of academic material support, learn by doing (allocation of more time for internship), more interaction with the academic staff, qualifications of the academic staff and sensitivity to individual learner types and learner backgrounds, the theme “expectations to create an international campus with a successful diversity management among students” includes attracting more students from different regions of the world, communication frameworks among students and graduates, high frequency of extra-curricular activities.
Keywords: Diversity Management; Academic Satisfaction Experience; Cultural Diversity; Internationalization